Gastroparesis Pathophysiology, Presentation and Treatment - Parkman, Henry P.; McCallum, Richard W. (Clinical Gastroenterology,, 2012)
Gastroparesis is an increasingly recognized disorder. Treatment can be difficult due to the several mechanisms for symptom production. Gastroparesis: Pathophysiology, Presentation and Treatment serves as a concise reference on this disorder that allows clinicians to quickly access and evaluate the necessary information for treating and managing patients with gastroparesis. Each chapter is written by experts in their respective area. The volume will enable the reader to better understand all aspects of this disorder. The book presents current concepts in a variety of areas opening with the epidemiology, clinical presentation and pathophysiology of gastroparesis. The natural history of patients is explored as well as evaluation of patients with suspected gastroparesis. This section includes chapters on Wireless Capsule Motility, Electrogastrography and Antroduodenal Manometry. This important resource concludes with a full section on treatment including dietary, prokinetic, antiemetic, sensory, electric stimulation, and surgical methods. New developments include the use of gastric electric stimulation for treatment, the use of SmartPill for diagnosis, and a number of new agents in development for this disorder. Gastroparesis: Pathophysiology, Presentation and Treatment is the ideal reference for gastroenterologists, and also for surgeons, endocrinologists, primary care physicians and nutritionists looking to keep pace with the latest information treatment options for their patients.